First-principles study of structure, initial lattice expansion, and pressure-composition-temperature hysteresis for substituted LaNi5 and TiMn2 alloys. (2nd November 2016) - Wong, D F; Young, K; Ng, K Y S
Abstract: The c / a unit-cell aspect ratios of CaCu5 -structured AB5 and C14 Laves phase AB2 metal hydride alloy families are generally correlated to pressure-concentration-temperature hysteresis and degree of alloy pulverization. Structures of substituted LaNi4 X and C14 Ti4 Mn7 X compositions and their hydrides in the α -phase were calculated by first principles using density functional theory to look at the c / a ratio and its relationship to initial lattice expansion. Lattice expansion with respect to the lattice parameters and lattice volume in the α -phase hydrides were analyzed, and a general trend in lattice expansion in the direction of higher resistance to elastic deformation was observed to correlate well to the trends in hysteresis measured in AB5 and C14 AB2 type alloys. Lattice expansion is noted to induce microstrains within the crystal lattice, and the anisotropy in the LaNi4 X and Ti4 Mn7 X alloys played a role in determining the direction of higher resistance to deformation. Lattice expansions both measured and calculated have been linked to capacity degradation measurements as well as to hysteresis (a measure of irreversible energy losses due to lattice plastic deformation), which may be related to the dislocations and defects formed during hydrogenation.